Diagnostic Methods in Forensic Pathology: Autoptic Findings and Immunohistochemical Study in Cases of Sudden Death Due to a Colloid Cyst of the Third Ventricle - Angelo Montana; Francesco Paolo Busardò; Giovanni Tossetta; Gaia Goteri; Pasqualina Castaldo; Giuseppe Basile; Giulia Bambagiotti (Diagnostics, 2024)
The colloid cyst is a non-malignant tumor growth made of a gelatinous material covered by a membrane of epithelial tissue. It is usually located posterior to the foramen of Monro, in the anterior aspect of the third ventricle of the brain. Due to its location, it can cause obstructive hydrocephalus, increased intracranial pressure, and sudden cardiac death, catecholamine-mediated, through hypothalamus compression. All the mechanisms are still controversial, but the role of catecholamine has been confirmed with histological findings that highlighted myocardial injury (coagulative myocytolysis and contraction band necrosis, CBN). This study presents a case of sudden death in a previously healthy 22-year-old male due to a colloid cyst of the third ventricle. A complete autopsy was performed, highlighting in the brain an abundant quantity of cerebrospinal fluid (CSF) and a 2 cm pale grayish-green rounded cyst formation partially filling and distending the third ventricle. The diagnosis was confirmed through immunohistochemical investigation: positivity for Periodic acid-Schiff (PAS) staining and CK7 expression. In cases such as the one reported here, a combined approach of autopsy, histology, and immunohistochemistry is mandatory in order to identify the neoformation’s location and morpho-structural characteristics for a correct differential diagnosis, as well as to identify the cause of death.